Hubungan Dinamis Arus Modal Asing, Nilai Tukar Rupiah dan Pergerakan Indeks JII 30 dengan Metode Pendekatan Vector Autoregressive (VAR) pada Masa Pandemi Covid 19 - Muhammad Suhaidi; Winda Anggraini; Hendra Novian; M. Nasor; Nina Ayu Puspita Sari (ITB AAS INDONESIA Surakarta, 2022)
This study was conducted to determine the dynamic relationship of foreign capital flows, the rupiah exchange rate and the movement of the JII 30 index. The type of research used is quantitative research with the Autoregressive vector analysis (VAR) method using daily time series data for the period March-December 2019 to March-December. 2020 with the help of the eviews 9. Data collection was carried out using secondary data in the form of published reports from websites related to research. The population of this study are companies listed in the Jakarta Islamic Index (JII). The sampling technique used in this research is the saturated sample technique. The number of companies that were sampled in this study were 30 companies. Granger causality test results show that the variable of foreign capital flows has a one-way relationship with the rupiah exchange rate, where foreign capital flows affect the rupiah exchange rate in Indonesia. Then the variable of foreign capital flows also has a one-way relationship with the JII 30 movement index. Where foreign capital flows affect the JII 30 movement index, as well as the rupiah exchange rate variable has a one-way relationship with the JII 30 movement index. Where the JII 30 index affects the exchange rate. rupiah. The results of another study using the cointegration test show that the variables of foreign capital flows, the rupiah exchange rate and the JII 30 movement index have a long-term equilibrium relationship. Foreign capital flows and the rupiah exchange rate before and before covid 19 did not affect each other, while the rupiah exchange rate before and before covid 19 affected the JII 30 index.